Implementasi Pembelajaran Agama Islam Pada Peserta Didik Muslim di SMP Kristen 2 Bandar Jaya - Khasanah, Nurul (PPSDP Undergraduate Journal of Educational Sciences, 2024)
This research was designed to conduct research on fulfilling the rights of Muslim students in receiving religious education at SMP Kristen 2 Bandar Jaya. Because basically every educational unit at all pathways, levels and types of education is obliged to provide religious education. The research results show that the implementation of religious education at SMP Kristen 2 Bandar Jaya uses 2 double curricula, so that the assessment follows 2 different curricula, namely the 2013 Curriculum and KTSP. The PAI teacher's teaching method at SMP Kristen 2 Bandar Jaya uses lecture, discussion, question and answer and practice methods. Referring to Law No. 20 of 2003 concerning the National Education System in article 12 paragraph 1 point a concerning the right of every student to receive religious education according to their religion and taught by teachers of the same religion, the fulfillment of the right to receive religious education for Muslim students in junior high school Kristen 2 Bandar Jaya has not been fulfilled optimally. Even though there are PAI subjects, they cannot meet the need for religious education. This is because PAI learning generally teaches tolerance between religious communities, whereas there is no deepening of religion. Apart from that, at Bandar Jaya Christian Middle School 2, PAI subjects are taught by Muslim teachers. However, the facilities and infrastructure for Muslim students are inadequate.